Sistem Pendukung Keputusan Penentuan Penerimaan Bantuan Pangan Non Tunai Menerapkan Metode Simple Additive Weighting (SAW) - Muhammad Fikri; Fauriatun Helmiah; Pristiyanilicia Putri (Building of Informatics, Technology and Science (BITS), 2022)
One of the programs established by the government to reduce the burden on the community in meeting basic needs is the Non-Cash Food Assistance Program (BPNT). The Social Service of Batu Bara Regency in determining the acceptance of Non-Cash food assistance has so far been using conventional methods. This makes it less than optimal in determining which people are eligible for this selection of food aid recipients, especially the priority of several people whose names have been registered with the Batu Bara Regency Social Service. In doing this election calculation does not use specific criteria so that the alternatives obtained are not as expected. Besides that, it takes time that is not fast in determining decisions and the results are slow because it must be done by holding a meeting between employees and the head of the department which causes the results of the decision to be not on target. So the Social Service of Batu Bara Regency needs a decision support system to provide alternative choices and make it easier to determine prospective Beneficiary Families (KPM) participants to determine decision assessments for Non-Cash Food Aid Reception. The method used is by collecting data on filling out forms given to village communities and using the implementation of the Simple Additive Weighted (SAW) method as a decision support system in receiving non-cash food assistance at the Batu Bara District Social Service. The results of this research are the best with the highest score with a number of criteria, the chosen one is the name Lestari, who deserves to be recommended as receiving non-cash food assistance, there are also several other names based on the ranking in the calculation of this SPK